(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
درسنا إمكانية تشكيل معقد ملون بين pb وكاشف ثنائي فينيل كاربازيد DPCHلتطوير طريقة طيفية استخلاصية لتحديد الرصاص، وجدنا أن الكاشف المذكور لا يشكل مع الرصاص معقداً مستقراً في الوسط المائي بل في الطور العضوي والذي يظهر بلون أحمر بنفسجي بعد استخلاصه بمزيج كلوروفورم : بيريدين (1 : 3)، pH = 8.3 بوجود محلول واقي من البورات . دلت الدراسة التجريبية لطيف امتصاص محلول المعقد أن ، كما حددنا كافة القرائن الكمية المتعلقة بهذا المعقد حيث بلغت نسبة التفاعل بين DPCH وشاردة الرصاص (1:1) ومعامل الامتصاص الجزيئي 3.8 ×104 l.mol-1.cm-1 = ε وثابـت تشكل المعـقد βK = 6 ×103، درسنا أيضا كافة العوامل المؤثرة في تشكل المعقد وثبات امتصاصيته. كان قانون بير – لامبرت محققاً ضمن المجال ( 0.1 – 2 ) mg/l. استخدمنا الطريقة المقترحة في تحليل عينات تجريبية مأخوذة من محاليل قياسية لشاردة الرصاص. ولم يتجاوز الانحراف المعياري النسبي المئوي القيمة 2.59 % ولم تقل الاسترجاعية عن 96.6 % مما يؤكد إمكانية استخدام الطريقة المقترحة للأغراض التحليلية . The possibility of formation a colored chelate between pb and 1,5- diphenyl carbazide (DPCH) was studied to develop an extraction spectrophotometric method for lead determination. The reagent reacts in borate buffer (pH= 8.3) to give a red-violet chelate after extraction with chloroform : pyridine (1:3), which has an absorption maximum at 522nm.The stoichiometric composition of chelate is Cpb: DPCH = (1:1). The molar absorptivity and chelate constant formation were found to be 3.8 ×104 l.mol-1.cm-1 and 6×103 respectively. and we have studied all factors which affect on the complex formation and stability of its absorbance. Beer- Lambert was obeyed within the rang ( 0.1-2 ) mg/l. The developed method was examined on lead standard solutions (RSD< 2.59 %, recovery >96.6). All results ensure the analytical possibility of the developed method.